An ANALYSIS OF INTERNET BASED LEARNING DURING COVID-19 PANDEMIC IN EFL CLASSROOM - CUCUM ROHMAWATI (FKIP, Universitas Banten Jaya, 2021)
Indonesia is in Pandemic of Covid-19 which make many activities should be limited to stop the spread of virus and decrease the number of victims and death. The government implemented a new policy that is work from home and study for home for students in all education institution, includes vocational high school which students are EFL learners. Teaching learning activities should be implemented although the teachers and students are in different places. So, internet based learning should be used. Therefore, this article aims to give an analysis of internet based learning during Covid-19 Pandemic in EFL Classroom. The result found that in implementing internet based learning is ineffective due to some problems, they are students inactive, internet tools, internet access or quota and also control from stakeholders. Dealing with those problems, the teachers can implement several ways to make internet based learning more effective and students can comprehend their English skill although they don’t learn directly. The ways that teacher should try consist of: (1) doing exploration, (2) doing enactment, and the last (3) doing evaluation.